A comparative analysis of Shariah stock screening methodology for securities commission Malaysia and major international Shariah index providers - Md. Sawari, Mohd. Fuad; Sitiris, Miszairi; Artalim Zaim, Muntaha (International Islamic University Malaysia, 2024)
This article reviews and compares the Shariah stock screening methodologies adopted by the Securities Commission (SC) of Malaysia and major international Shariah index providers including Dow Jones Islamic Market World Index (DJIM), Financial Times Stock Exchange Islamic Index Series (FTSE), Standard & Poor’s Shariah Index (S&P), and Morgan Stanley Capital International Islamic Index (MSCI). Qualitative methods are used to assess the Shariah stock screening methods and standards practiced by these five renowned institutions. A comparative analysis scrutinizes the variances between these methods and principles. The study reveals both similarities and differences in the Shariah stock screening methodologies developed by the five institutions. In general, all utilise a two-tier screening method involving qualitative and quantitative filters. Comparing the qualitative screening practices shows some institutions are more specific in listing Shariah non-compliant activities, while others take a more general approach in permitting business activities to be Shariah compliant. For quantitative screening, the allowable threshold ratios differ slightly between institutions. Overall, the language has been simplified and made more concise while preserving the key information.